Criminal Liability for Traffic Accident Perpetrators with Schizophrenia - John Piter Tampubolon; Natsir Asnawi (Journal Customary Law, 2026)
The high number of traffic accidents in Indonesia is still narrowly understood as legal events oriented towards physical victims and material losses, while the psychological impact experienced by witnesses and indirect victims has not received adequate attention in the construction of criminal law. This condition becomes increasingly problematic when accidents involve perpetrators with mental disorders, particularly schizophrenia, because positive law does not provide clear and consistent regulations regarding criminal liability and the actions that can be imposed. The National Criminal Code, through Law Number 1 of 2023, does introduce the concept of action against perpetrators who are unable to take responsibility, but the use of the phrase "can be subject to action" in Article 39 actually opens up space for legal uncertainty and excessive discretion. This study aims to analyze the weaknesses in the legal construction of criminal liability in traffic accidents involving perpetrators with schizophrenia and formulate a more just and humane normative reconstruction model. The method employed is normative legal research with a statutory and conceptual approach, which examines the principle of fault, the theory of criminal liability, and the relationship between criminal law and mental health law. The research findings indicate that the absence of standards for assessing capacity for responsibility and the lack of firm norms for action have the potential to lead to inconsistent law enforcement and neglect the interests of victims and the protection of perpetrators' human rights. This research proposes a reconstruction of criminal responsibility based on the separation of criminal acts and capacity for responsibility, strengthening the role of forensic psychiatry, and implementing a criminal and action system oriented toward substantive justice.